1997
DOI: 10.1046/j.1365-2435.1997.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in haematological parameters in relation to prey switching in a wild population of harbour seals

Abstract: 1. Previous studies have found marked inter‐annual variation in winter food availability, diet composition and body condition in a population of harbour seals (Phoca vitulina L.) in Northeast Scotland. This study aimed to determine whether there were other physiological consequences of prey switching by comparing haematological parameters in years when the clupeids herring and sprat dominated the diet and in years when seals switched to alternative prey. 2. There were significant differences in leukocyte and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…The relationships observed here between hematological parameters and contaminants may be best seen as indicative of sentinel responses to contaminant exposure, responses that were not necessarily pathologic. Hematological parameters of marine mammals also can be affected by parasite load, diving behavior, stress, dietary shifts, and other individual differences (Bryden & Lim, 1969;Roletto, 1989;Geraci & Medway, 1993;Thompson et al, 1997). If such factors covaried with contaminant levels, it would not be possible to distinguish their relative contributions or causal proximity to alterations in hematological parameters.…”
Section: Hematology and Contaminant Levelsmentioning
confidence: 99%
“…The relationships observed here between hematological parameters and contaminants may be best seen as indicative of sentinel responses to contaminant exposure, responses that were not necessarily pathologic. Hematological parameters of marine mammals also can be affected by parasite load, diving behavior, stress, dietary shifts, and other individual differences (Bryden & Lim, 1969;Roletto, 1989;Geraci & Medway, 1993;Thompson et al, 1997). If such factors covaried with contaminant levels, it would not be possible to distinguish their relative contributions or causal proximity to alterations in hematological parameters.…”
Section: Hematology and Contaminant Levelsmentioning
confidence: 99%
“…However, nutritional quality and diet composition may also be important. Thompson et al (1997b) reported that in years when harbour seal diet in the Moray Firth was dominated by gadoids and cephalopods, health and body condition indices in adults and yearlings were significantly lower, compared to years when clupeids were the most important prey species. These nutritional requirements may also be important factors affecting prey selection and foraging in harbour seals.…”
Section: Interspecific Differences In Seal Dietmentioning
confidence: 99%
“…As such, species with generalist diets, variable foraging behaviours and many reproductive strategies tend to be buffered from catastrophic environmental shifts that put specialist species at a higher risk of extinction when population sizes are low (Pimm 1991, McKinney 1997, Kotze & O'Hara 2003. In the marine environment, plasticity in foraging behaviour and diet has been demonstrated for many different higher vertebrate taxa including seabirds (Votier et al 2004), marine mammals (Thompson et al 1997, Harcourt et al 2002 and some fish species (Ellis et al 1996, Garrison & Link 2000, Bellwood et al 2006.…”
Section: Introductionmentioning
confidence: 99%